Two intrauterine rescue transfusions in treatment of severe fetomaternal hemorrhage in the early third trimester. Issue 2 (12th November 2013) - Stefanovic, Vedran; Paavonen, Jorma; Halmesmäki, Erja; Luukkainen, Päivi; Tikkanen, Minna; Nuutila, Mika; Poikkeus, Piia
Key Clinical Message When massive fetomaternal hemorrhage is diagnosed in the early third trimester of pregnancy, serial fetal intravascular transfusion may be an alternative to immediate delivery.